Simulation of paleotectonic stress fields and quantitative prediction of multi-period fractures in shale reservoirs: A case study of the Niutitang Formation in the Lower Cambrian in the Cen'gong block, South China. (June 2017) - Liu, Jingshou; Ding, Wenlong; Wang, Ruyue; Yin, Shuai; Yang, Haimeng; Gu, Yang
Abstract: Reservoirs where tectonic fractures significantly impact fluid flow are widespread. Industrial-level shale gas production has been established from the Lower Cambrian Niutitang Formation in the Cen'gong block, South China; the practice of exploration and development of shale gas in the Cen'gong block shows that the abundance of gas in different layers and wells is closely related to the degree of development of fractures. In this study, the data obtained from outcrop, cores, and logs were used to determine the developmental characteristics of such tectonic fractures. By doing an analysis of structural evolution, acoustic emission, burial history, logging evaluation, seismic inversion, and rock mechanics tests, 3-D heterogeneous geomechanical models were established by using a finite element method (FEM) stress analysis approach to simulate paleotectonic stress fields during the Late Hercynian—Early Indo-Chinese and Middle-Late Yanshanian periods. The effects of faulting, folding, and variations of mechanical parameters on the development of fractures could then be identified. A fracture density calculation model was established to determine the quantitative development of fractures in different stages and layers. Favorable areas for shale gas exploration were determined by examining the relationship between fracture density and gas content of three wells. The simulation results indicate the magnitude of minimum principal stress during the Late Hercynian — Early Indo-Chinese period within the Cen'gong block is −100 ∼ −110 MPa with a direction of SE-NW (140°–320°), and the magnitude of the maximum principal stress during the Middle-Late Yanshanian period within the Cen'gong block is 150–170 MPa with a direction of NNW-SSE (345°–165°). During the Late Hercynian — Early Indo-Chinese period, the mechanical parameters and faults play an important role in the development of fractures, and fractures at the downthrown side of the fault are more developed than those at the uplifted side; folding plays an important role in the development of fractures in the Middle-Late Yanshanian period, and faulting is a secondary control. This 3-D heterogeneous geomechanical modelling method and fracture density calculation modelling are not only significant for prediction of shale fractures in complex structural areas, but also have a practical significance for the prediction of other reservoir fractures. Highlights: The classification, developmental characteristics, and formation timing of fractures in the Niutitang shale. Spatial distribution characteristics of mechanical parameters in the Niutitang shale. Three-dimensional heterogeneous geomechanical modelling. A fracture density calculation model for prediction of fracture density in different periods and layers. Distribution characteristics of multi-period tectonic fractures in the Niutitang shale.